Configuration strategy of shared mitigation equipment for voltage sag considering the demands of users. Issue 25 (6th January 2021) - Wang, Ying; Yang, Yixuan; Xiao, Xianyong; Zheng, Zixuan; Yang, Hang
Abstract : It is an effective way to mitigate voltage sag by equipping custom power devices in premium power park (PPP), and the key lies in the balance between technology and economy. This study proposes a method to mitigate voltage sags to meet the needs of different sensitive users in PPP to ensure the mitigation effect and reduce mitigation costs. Firstly, a strategy of shared mitigation equipment (ME) and its operation mode is presented, including the multiple stakeholders, the structure of shared ME, and the scheme of the switch on/off to improve the utilisation rate of ME. Secondly, a sensitive equipment (SE) grouping method is proposed, which is suitable for shared ME strategy, considering the minimum compensation voltage magnitude and the economic loss caused by voltage sag. Meanwhile, this study proposes an assessment method of SE failure probability based on the three‐parameter Weibull function to design the capacity of ME reasonably. Thirdly, a multi‐objective collaborative optimisation model is established based on economic loss assessment to maximise the net income of investors and users. Finally, the effectiveness of the proposed method has been proved through the case study of two sensitive users in PPP.